Effectiveness of Natural Coagulant in Coagulation Process: A Review - Hariz Amran, Amir; Syamimi Zaidi, Nur; Muda, Khalida; Wai Loan, Liew (International Journal of Engineering and Technology, 2018)
Natural coagulants have been increasingly popular in the past few years due to its benefits and the fact that it resolves most of the associated problems when using chemical coagulants. Plant-based natural coagulants perform coagulation either by polymer bridging or charge neutralization, it can be extracted from various plant components. Concerted research and development efforts have been conducted in discovering new plant species and constituents that can be used as natural coagulants, which further boosting the effectiveness of existing plant-based natural coagulants.Â The objective of this paper is to provide a mini review on studies done over the span of ten years regarding plant-based natural coagulants. This paper also includes advantages and disadvantages of natural coagulants prior to identify several potential research gaps to provide platform towards the need of further study.Â Â